Normotensive trauma patients with renal injuries: Hidden candidates for massive transfusion - Xin‐Hong Lin; Pi‐Chieh Lin; Ching‐Hua Tsai; Wei‐Ti Su; Shiun‐Yuan Hsu; Ching‐Hua Hsieh (Hong Kong Journal of Emergency Medicine)
Abstract Background Early identification of trauma patients requiring massive transfusion (MT) is crucial for improving outcomes. However, current scoring systems may overlook patients with initially stable vital signs who later require MT. This study aimed to identify anatomic risk factors for MT in relatively stable trauma patients upon emergency department arrival. Methods This retrospective study analyzed data from 22,159 adult trauma patients admitted to a level I trauma center between 2011 and 2020. Patients were stratified by systolic blood pressure (SBP) and MT status. MT was defined as ≥10 units of blood products within 24 h. Demographics, injury characteristics, vital signs, laboratory results, and outcomes were compared between groups. Results Out of 22,159 patients 241 (1.1%) required MT. Among MT patients, those with initial SBP ≥ 90 mmHg (n = 170) showed significantly higher rates of renal injuries (8.8% vs. 1.4%, p = 0.035) compared to those with SBP < 90 mmHg (n = 71). Furthermore, among patients who did not receive massive blood transfusion (n = 21,918), stratified by SBP status, the patients with SBP < 90 mmHg exhibited a significantly higher prevalence of renal injuries compared to those with SBP ≥ 90 mmHg (3.2% [n = 12/370] vs. 0.5% [n = 117/21,548], p < 0.001) with an odds ratio of 6.14 (95% CI: 3.36–11.22). Notably, mortality rates were similar between normotensive and hypotensive MT patients (38.2% vs. 32.4%, p = 0.391). Conclusion Trauma patients presenting with stable blood pressure but renal injuries may still require MT. Clinicians should maintain a high index of suspicion for occult blood loss in these patients, even when initial vital signs appear stable. This study highlights the need for vigilant monitoring and management of seemingly stable patients with specific injury patterns to prevent delayed MT initiation.